Berat beban tas dengan keluhan musculoskeletal pada siswa SMA - Yunita Sari Purba; Putri Winda Lestari (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Schoolbag-weights and musculoskeletal complaints among high-school students in Jakarta, IndonesiaBackground: Most of high school students every day carry a schoolbag-weights of approximately 5-7 kg from home to school within 3 years study time, it can trigger the emergence of Musculoskeletal disorders (MSDs), which is a collection of symptoms / disorders related to muscle tissue, tendons, ligament, cartilage, nervous system, bone structure, and blood vessels. MSDs can cause disruption of daily activities, concentration of learning, and learning achievement.Purpose: To determine the effects of School Bag-weights and musculoskeletal complaints among high-school students in Jakarta, Indonesia.Method: An analytic observation with cross-sectional approach. The population was all high school students at east Jakarta with the sample student in grade XI of 370 students and taken by simple random sampling. The independent variable is the Schoolbag-weights, while the dependent variable is MSDs. Retrieval of data by filling out the Nordic Body Map questionnaire. Data processed univariate and bivariate with the Spearman test.Results: There was an effect of schoolbag-weights and musculoskeletal complaints among high-school students in Jakarta, Indonesia. Spearman correlation analysis results, got p=0.000 with r=0.225, which means there is a weak correlation between schoolbag-weights with musculoskeletal complaints. The direction of the positive correlation that means the heavier the schoolbag that they carry would follow by a higher the musculoskeletal complaints, and vice versa.Conclusion: There is a correlation between school bag-weights and musculoskeletal complaints among high-school students in Jakarta, IndonesiaKeywords: Schoolbag-weights; Musculoskeletal complaints; High-school studentsPendahuluan: Siswa SMA setiap hari memikul beban pada bagian tubuh belakang kurang lebih 5-7 kg setiap selama jangka waktu 3 tahun selama studi, hal tersebut dapat memicu munculnya Musculoskeletal disorders (MSDs) yaitu sekumpulan gejala/gangguan yang berkaitan dengan jaringan otot, tendon, ligament, kartilago, sistem saraf, struktur tulang, dan pembuluh darah. MSDs dapat menyebabkan gangguan kegiatan sehari-hari, konsentrasi belajar dan prestasi belajar.Tujuan: Mengetahui seberapa besar berat tas berpengaruh terhadap risiko musculoskeletal disorder. Metode: Analitik observatif dengan pendekatan cross-sectional. Populasi adalah seluruh siswa SMA di wilayah Kec. Kramat Jati Jakarta Timur sebanyak 4.708 siswa dengan sampelnya siswa kelas XI sebanyak 370 siswa, diambil secara simple random sampling. Variabel bebas adalah berat tas sedangkan variabel terikat adalah MSDs. Pengambilan data dengan pengisian kuesioner. Data diolah secara univariat dan bivariat dengan uji korelasi spearman. Hasil: Didapatkan korelasi antara berat tas dengan musculoskeletal disorder. Hasil Analisis Korelasi Spearman antara berat tas dengan keluhan nyeri otot, didapatkan nilai p=0.000 dengan nilai r=0.225 yang artinya terdapat korelasi yang lemah antara berat tas dengan keluhan nyeri otot. Arah korelasi positif menunjukkan bahwa semakin berat beban tas maka keluhan nyeri otot makin tinggi, begitu juga sebaliknya. Simpulan: Berat beban tas berkorelasi dengan keluhan Musculoskeletal disorders (MSDs).